Human muscle and spinal activation in response to body weight loading. Issue 5 (31st January 2023) - Clarke, Benjamin; Al‐Hammdany, Jannah Khalid; Di Giulio, Irene
Abstract: Human standing is the anatomical and functional framework for independent movement. The study of weight bearing during standing and movement is crucial to support the development of technology aimed at restoring independent gait, where unsupported weight bearing is still elusive. This study aims to determine muscle and spinal activation at different gravitational loads in young, healthy individuals to provide potential patterns of spinal stimulation for standing. Muscle activity was recorded with surface electromyography (EMG) from 18 healthy participants at different body angles while on a motorised plinth. The body angles tested and the relative gravitational loadings were: 0 deg (supine) corresponding to ~0% of total body weight (BW), 15 deg (~26% BW), 30 deg (~50% BW), 45 deg (~71% BW), 60 deg (~87% BW), 75 deg (~97% BW), upright on and off the plinth (~100% BW). The muscles recorded were soleus, gastrocnemius medialis and lateralis, tibialis anterior, adductor longus, peroneus longus, vastus medialis and lateralis, rectus femoris, sartorius, extensor digitorum longus, semimembranosus, semitendinosus, biceps femoris, gracilis, rectus abdominis, external oblique, erector spinae and latissimus dorsi. From the recorded muscle activity, spinal activation maps were calculated. Despite high variability in EMG data, the group muscle activity changed with body angle. Vastus lateralis became activated at 60 deg (~87% BW), soleus became activated at 75 deg, and the gastrocnemii at 90 deg. The spinal segments that showed significant differences in mean activation between angles were the fifth lumbar L5 and the first sacral S1 segments. The data from this study suggest that weight‐bearing independent standing could be achieved with increased activation of a limited number of superficial muscles tested, and 87% BW is a critical loading for increased muscle activation compared to the supine position. The spinal activation in the lower lumbar and sacral segments shows the involvement of these regions in maintaining weight‐bearing standing. By reproducing this pattern of muscle and spinal segment activity through tonic stimulation, we speculate that restoration of independent standing and walking may be possible for patients following spinal cord injuries. Abstract : Muscle activity was recorded with surface electromyography to determine spinal activation at different gravitational loads. The fifth lumbar and first sacral segments were involved in maintaining weight‐bearing standing.